Occupation of Household Heads as Correlate of Child Care Practices of Low-Income Households - Guillasper, Jean (JPAIR Multidisciplinary Research, 2015)
Child care is considered as an integral part of society's health. This study was conducted to determine the child care practices of households with very low socio-economic status in Singalat, Palayan City, Nueva Ecija, Philippines. The researcher utilized the descriptive method of research coupled with questionnaire as a tool for data gathering. The respondents were chosen by means of purposive sampling technique and the data gathered were treated with frequency and percentage distribution, weighted mean and Pearson Product Moment Correlation. The results showed that the respondents were living in a mixed neighborhood; houses were built in light and cheap materials, poorly constructed, unpainted and dilapidated. The majority of the household heads were unskilled workers while some were employed as blue collar workers or engaged in manual labor that receives an hourly rate of pay, high school graduates with 0-1 or few facilities with monthly family income of P1,000.00 (23 USD) and below. The socio-economic classification of the respondents falls under E or "very low socio-economic classification" with a score of 7-14 based on MORES-SEC Classification of Households. Child care practices in terms of nutrition, hygiene, disease prevention and health restoration were "every often accomplished" by the respondents. The "occupation" of household heads plays a vital role in the delivery of child care among the family respondents. Occupation means income, while income would mean food, shelter, clothing, medicine or health and other basic necessities of a growing child.
Keywords: Social Science; child care practices; socio-economic status; descriptive-survey; Nueva Ecija; Philippines